E-pharmacophore-based screening of mGluR5 negative allosteric modulators for central nervous system disorder. (February 2019) - Vijaya Prabhu, Sitrarasu; Singh, Sanjeev Kumar
Abstract: Glutamate, a major neurotransmitter in the central nervous system of human, plays a crucial role in various neurological pathways by activating the ligand-gated ion channels such as mGluR and iGluR. Dysfunction of mGluR 5 can cause Alzheimer's disease, Parkinson's disease, epilepsy, depression, anxiety, etc. In the current study, we have developed the energetically optimized pharmacophore model to screen the eMolecules database having more than 6 million compounds with the help of reported cocrystal structure with 3-chloro-5-[6-(5-fluoropyridin-2 yl)pyrimidin-4-yl]benzonitrile (PDB ID: 5CGD). The obtained hits were docked into the allosteric site of the target and further validation of E-pharmacophore was done by enrichment calculations followed by the molecular dynamics simulations to analyze the specific amino acid interactions with the compound present in the allosteric site of the receptor.